Sejarah Dan Kaidah Jarh Wa Al-Ta'dil - Tangngngareng, Tasmin; S. Puyu, Darsul; Perdana Rayyn, I Gusti Bagus Agung (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2021)
This article discusses the history and rules or theoretical basis of al-jarh} wa al-ta'di>l as a branch of science that has an important role in the science of hadith. In this article, there are two important topics that will be the subject of discussion, namely, those related to the history of the science of al-jarh} wa al-ta``di>l and the rules of al-jarh} wa al-ta'di>l. Therefore, it is necessary to explain this so as not to cause a mistake in understanding it by conducting a historical study based on a literature review. So the conclusion is that al-jarh} wa al-ta'di>l started at the time of the Prophet. and continues to grow until the generation of tabi' al-ta>bi'i>n, even after. The rule of al-jarh} wa al-ta'di>l is a method or analytical knife used for problem solving in criticizing the sanad of hadith which is the object of research. Keywords: History, Rule, al-Jarh}, al-Ta‘di>l